Praying the Imprecatory Psalms? Reflections on an Unresolved Theological Problem with Dietrich Bonhoeffer - Hamilton, Nadine (International Journal of Systematic Theology, 2022)
This article probes the question of whether or not the so-called imprecatory Psalms may be prayed either in private settings or churches. In his Finkenwalde sermon on Psalm 58, Dietrich Bonhoeffer considers them 'the prayer[s] of the innocent'. This article examines Bonhoeffer's understanding and handling of the imprecatory Psalms, which leads to the overall question of the theology of Scripture - in particular, the theological significance of the use of the Psalms as Christian prayer. This in turn leads to questions concerning the theological presuppositions, context, and implications of christological readings of the Old Testament, and last but not least the relationship between Scripture, incarnation and the cross. It is my argument that Bonhoeffer's understanding of Jesus Christ is the hermeneutical key to Scripture. This must be elaborated in order to see how human prayer can also be the prayer of Jesus Christ at the same time. Only from there can one understand how, according to Bonhoeffer, in Christ the Christian can also pray the imprecatory Psalms.
CRIS-Team WoS Importer:2022-03-18